A new model for evaluating the compatibility of multi-coal seams and its application for coalbed methane recovery. (1st June 2022) - Chen, Yuhua; Luo, Jinhui; Hu, Xunyu; Yang, Yongguo; Wei, Chongtao; Yan, Heping
Graphical abstract: Highlights: A new model on the compatibility of multi-coal seams was established to evaluate the compatibility intensity of multi-coal seams. A cross-correlation matrix was calculated to form a cross-correlation map describing the compatibility indexes of multi-coal seams. With basic data of two experimental wells in western Guizhou, two segmentation schemes were provided by the cross-correlation maps of compatibility indexes. Finally, detailed analysis of drainage performance of Well M-1 and M-2 indicated that the segmentation was suitable for the actual performance of exploration. Abstract: The coproduction of coalbed methane(CBM) in multi-coal seams is an effective model for increasing CBM production, which was successfully practiced in many CBM projects. During coproduction, appropriate segmentation of multi-coal seams is critical for the high production of CBM projects. To obtain an appropriate segmentation scheme, a new model was established to evaluate the compatibility intensity of multi-coal seams by the pressure distribution of a double-layered status equation. Then the pressure domains of the model were divided into six regions to select the sections that quantify the compatibility intensity of multi-coal seams. Furthermore, a cross-correlation matrix was calculated to form a cross-correlation map describing the compatibility indexes of multi-coal seams. The model was applied to two experimental wells(Well M-1 and M-2) in western Guizhou province to evaluate its performance. Well M-1 was divided into four segments and Well M-2 into three segments. Finally, the detailed analysis of drainage performance of Well M-1 and M-2 indicated that the segmentation was suitable for the actual performance of exploration.